Digital literacy as a tool for empowerment and community inclusion - Palmeiro, Ricardo (2021)
Since the emergence of the new information and communication technologies, a new social gap has appeared, between those who know how to use the new technologies and those who don't: the digital divide. As a way to overcome this gap, international organizations have made a series of recommendations for governments to create digital inclusion programs to empower the population in need of technological knowledge. Since the end of the last century, governments (local, regional, national) have begun to create these programmes, with greater or lesser success, whose initial objective of technological training has evolved to the development of skills that allow the individual to fully develop his/her digital citizenship. This PhD dissertation started with this research question: What is the effect of digital inclusion programmes on the level of digital literacy of individuals and on greater participation community? It seeks to analyse the influence of Digital Literacy as a mechanism to reduce social exclusion and enhance individual and community development, as well as to create a theoretical model for analysing the influence of Digital Literacy on the individual and the community. The main theoretical pillars on which the study is based are in the field of Digital Literacy and Informational, the digital divide, digital citizenship and digital inclusion in different areas of education systems (formal, non-formal, informal). The empirical study consists in the analysis of two cases, the Internet Access Spaces in Alentejo (Portugal) and the KZgunea in the Basque Country (Spain), in three dimensions: Public Policies and Digital Inclusion Programmes (Access) through Documentation Analysis; Monitors and facilitators of the centres (Usage), with the carrying out of personal interviews; Users of the centres with questionnaires carried out in person and online. We are currently finishing the analysis of the interviews and the writing of the theoretical chapters. We are also evaluating the close of application of the questionnaires due to COVID19. We have the intellect to deposit the dissertation in 2021.